ANTIHYPERTENSIVE TREATMENT WITH COMBINED DRUG OF LOSARTAN AND HYDROCHLOROTHIAZIDE - R. M. Linchak; K. M. Shumilova; A. D. Martinyuk; T. A. Gusaim; E. V. Semyonova; L. G. Zhirova; S. A. Boitsov (Рациональная фармакотерапия в кардиологии)
Aim:  to evaluate efficiency and safety of the combined antihypertensive drug Lozap Plus (50 mg losartan, 12,5 mg hydrochlorothiazide) in patients with arterial hypertension (AH) of I-III grade with high and very high cardiovascular risk. Material and methods: 30 patients with AH of I-III grade (13 men and 17 women aged 51.9±1.9) were observed. Patients received Lozan Plus (Zentiva, Czech Republic) 1 time in the morning during 12 weeks. Ambulatory blood pressure monitoring (ABPM), echocardiography, biochemical blood analysis were carried out, microalbuminuria (MA) was determined, quality of life was assessed. Results: After 2 weeks of therapy decrease in office systolic blood pressure (BP) was observed, and after 4 weeks - in diastolic BP. After 12 weeks of treatment decrease in BP became more significant. Target systolic and diastolic BP was reached in 83.3% and 90% of patients respectively. Decrease in systolic BP was observed in 24 hrs. (from 141.9±1.9 to 128.6±0.8 mmHg, p<0.001), in daytime (from 146.8±2.6 to 135.8±1.0 mmHg, p<0.01) and in nighttime (from 131.5±1.9 to 118.8±1.9 mmHg, p<0.001). Diastolic BP also decreased: in 24 hrs. (from 91.7±1.8 to 78.7±1.6 mmHg, p<0.05), in daytime (from 94.3±1.3 to 85.0±1.2 mmHg, p<0.05) and in nighttime (from 83.5±2.0 to 71.2±1.7 mmHg, p<0.01). Daily variability of BP, time index of BP and morning BP rise (from 37.6±2.0 to 23.9±1.9 mmHg, p<0.001) reduced. Normalization of daily profile of BP was observed in the majority of patients after 12 weeks of Lozap Plus therapy. Treatment resulted in reduction of number of patients with myocardial hypertrophy (from 50% to 30%, p<0.01), and of patients with diastolic dysfunction of left ventricle (from 43.3% to 30%, p<0.05). Therapy with Lozap Plus during 12 weeks was followed by decrease in MA from 56.7±1.1 mg/l to 9.0±0.5 mg/l. Lozap Plus demonstrated metabolic safety by assessing carbohydrate, lipid, nitric and electrolyte blood parameters. Increase in quality of life was observed by week 12 of treatment. Conclusion: Lozap Plus is efficient antihypertensive drug providing cardio- and nephroprotection, which doesn’t cause metabolic disturbances and improves quality of life of hypertensive patients.